Estudio clínico e histopatológico de la enfermedad de Von Recklinghausen en Cavidad Oral - Romero R., Roberto (2002)
Twelve Von Reck1inghausen cases were studied finding more incidence within the 31-40 years group, with an incidence of 50% (6 cases). In the intraoral area there was more incidence in the palate, (5 cases 41.7%) but in the type of lesion the peripherical modules were more frequent (8 cases, 66.6%). The peripherical nodules were like nipples, but in case 4 it was like papule of 8 to 10 mm of diameter. Tumors o diffuse masses were detected in 3 cases (25%) being subcutaneous along the nerve. It was observed in the hard palate a soft lesion with 20 mm of diameter which was the same color of the underlying mucous. In the radiographic examination it was found alveolar bone loss in 7 cases (58.3%) as found in the serial radiographies. Tumor was found in the periodontal ligament in 3 cases (25%), in the maxilla 2 cases (16.7%) with extensive osteolitic lesions. In the histopathology it was found a great number of enlarged typical Schwan cells with fusiform nucleus around the. vessels.